Analysis of the Chinese railway system as a complex network. (January 2020) - Wang, Wei; Cai, Kaiquan; Du, Wenbo; Wu, Xin; Tong, Lu (Carol); Zhu, Xi; Cao, Xianbin
Highlights: Complex network theories are applied to analyze Chinese railway network (CRN). CRN displays a typical small-world and core-periphery structure. CRN's core-periphery structure embodies obvious economic and geographical features. The core-periphery structure is strengthened by gravity model and urban planning. Abstract: This paper conducts a series of complex network analyses on the Chinese railway network (CRN), where nodes represent cities with rail stations and edges denote connections defined by transit services between cities. CRN is a small-world network with two-regime power-law distributions. This paper also encapsulates CRN into a multi-layer infrastructure with a core-periphery structure via the ''weighted k -core decomposition" method. The reasonability of cities contained in the core layer is generally consistent with the hub set identified by the gravity model. The core-periphery structure is also benchmarked by urban agglomeration development planning in China.